2013
DOI: 10.1111/aae.12019
|View full text |Cite
|
Sign up to set email alerts
|

The Neolithic period in the Central Region of the Emirate of Sharjah (UAE)

Abstract: Stratified sites at Jebel Faya in the Central Region of the Emirate of Sharjah provide evidence for successive 'facies' of the Neolithic period. The oldest faciesfound at FAY-NE 1yielded 14 C dates in the late ninth millennium cal BC and is characterised by blade arrowheads which are morphologically similar to PPNB points. With 14 C dates from the late eighth and early seventh millennia cal BC, a techno-complex of large flint artefacts from FAY-NE10 represents the second Neolithic facies in the area. A sheep t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…This evidence might imply a micro-nomadism model, with human groups moving seasonally from the coast to mountain valleys. This pattern was postulated for the early and middle Holocene period, when the climate and environment of the Arabian Peninsula were changing by the ITCZ shift (Drechsler, 2009: 71;Fleitmann et al, 2003;Sanlaville, 1992) and was reported by scholars working in different regions of south-eastern Arabia, with most theories assuming migrants from coastal regions were seasonally settling in the highlands in search of food, pastures for animals, or colder mountain climate during summer heat (see Beech, 2004;Biagi & Nisbet, 2006;Cleuziou & Tosi, 2007;Salvatori, 1996Salvatori, , 1996Uerpmann, 2003;Uerpmann & Uerpmann, 1996Uerpmann, Uerpmann & Jasim, 2000;Uerpmann et al, 2012). However, in the case of the Qumayrah valley, the archaeological evidence points to the Late Neolithic period, when the intensity of the monsoon declined (Drechsler, 2009: 71;Magee, 2014: 43).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence might imply a micro-nomadism model, with human groups moving seasonally from the coast to mountain valleys. This pattern was postulated for the early and middle Holocene period, when the climate and environment of the Arabian Peninsula were changing by the ITCZ shift (Drechsler, 2009: 71;Fleitmann et al, 2003;Sanlaville, 1992) and was reported by scholars working in different regions of south-eastern Arabia, with most theories assuming migrants from coastal regions were seasonally settling in the highlands in search of food, pastures for animals, or colder mountain climate during summer heat (see Beech, 2004;Biagi & Nisbet, 2006;Cleuziou & Tosi, 2007;Salvatori, 1996Salvatori, , 1996Uerpmann, 2003;Uerpmann & Uerpmann, 1996Uerpmann, Uerpmann & Jasim, 2000;Uerpmann et al, 2012). However, in the case of the Qumayrah valley, the archaeological evidence points to the Late Neolithic period, when the intensity of the monsoon declined (Drechsler, 2009: 71;Magee, 2014: 43).…”
Section: Discussionmentioning
confidence: 99%
“…V C 2013 Despite an often marginal position in prehistoric studies, coastal environments have been an important place of attraction for human settlements, increasing population and its dispersion, and have also become hotspots for cultural interaction and social change (Bailey, 2004). If this general model could be applied to Bronze Age populations practicing oasis agriculture, the question remains open for the Neolithic, for which few sites are known inland (Uerpmann et al, 2006(Uerpmann et al, , 2008(Uerpmann et al, , 2012. The large number of archaeological sites along the coast of the Gulf of Oman and the Arabian Sea testifies to the antiquity of the peopling of coastal environments in the region (Biagi, 1994).…”
mentioning
confidence: 99%
“…These 20 groups represent an unbiased taxonomic system in which both morphological and technological concepts are embedded. If these novel units are compared against the pre-existing types derived from published sources (Charpentier, 2008;Crassard, 2008;Crassard & Petraglia, 2014;Spoor, 1997;Uerpmann, Potts, & Uerpmann, 2009;Uerpmann et al, 2013;Zarins, 2001), the grouping determined by known traditional types is maintained. New sub-groups, however, tend to emerge across the dendrogram.…”
Section: Resultsmentioning
confidence: 99%
“…During the Early Holocene (tenth-eighth millennium BC), projectile weaponry in south-eastern Arabia is characterised by the development of points made on flakes or blade-like blanks retouched to obtain a tang at the base (Charpentier & Crassard, 2013;Charpentier et al, 2016;Crassard & Petraglia, 2014;Cremaschi & Negrino, 2002;Hilbert, 2014;Uerpmann et al, 2013). These arrowheads form three well-defined groups named Fasad, al-Haddah, Natif and Faya points (described in detail by Charpentier & Crassard, 2013;Charpentier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%